Observations of Mkn 421 during 1997 and 1998 in the energy range above 500 GeV with the HEGRA stereoscopic Cherenkov telescope system - Aharonian, Felix A.; Akhperjanian, A. G.; Andronache, M.; Barrio, J. A.; Bernlöhr, Konrad; Bojahr, H.; Calle, I.; Contreras, J. L.; Cortina, J.; Daum, A.; Deckers, T.; Denninghoff, S.; et al. (Astronomy and astrophysics, 1999)
Since its commissioning in fall 1996, the stereoscopic system of Imaging Atmospheric Cherenkov Telescopes (IACTs) of HEGRA, with an energy ﬂux sensitivity ν Fν at 1 TeV of 10−11 erg cm−2 s−1 for one hour of observation time, has been used to monitor the BL Lac object Mkn 421 on a regular basis. In this paper, we report detailed temporal and spectral information about the TeV characteristics of Mkn 421 in 1997 and 1998. We study the light curve, the shortest time scales of ﬂux variability, the differential spectra on a diurnal basis for several days with good γ-ray statistics, and the time-averaged energy spectrum. Special emphasis is put on presenting the data taken during the world-wide April 1997 multiwavelength campaign.
Gesehen am 24.11.2020